The Impact of Corporate Social Responsibility on Brand Awareness of Telecommunication Industry in Ghana - Salifu, Shaibu (International Journal Labs, 2023)
Background: Corporate Social Responsibility (CSR) has attracted a lot of attention from academics and CSR practitioners over the years. But there is no universally accepted definition of the term CSR. Aim: This paper examines the impact of corporate social responsibility (CSR) on brand awareness construct of brand equity. Method: Extant literature reveals that little is known about CSR activities during an industrial crisis like covid-19 pandemic, most of the available research works in this area were carried out on developed countries and in the case of the telecommunication industry in Ghana, the scope of studies appear narrow as individual telecommunication companies were used as case studies and reported findings are inconclusive. Convenience sampling procedure was employed in which questionnaires were administered to 800 respondents across the 16 regions of Ghana. The field data was analyzed using inferential statistics (OLS regression and correlation analysis) and descriptive statistics. Findings: The study found that both ethical and philanthropic responsibilities of CSR positively relate to brand awareness and brand loyalty constructs of brand equity of the telecommunication industry in Ghana at statistically significant levels.